2007
DOI: 10.1038/emm.2007.11
|View full text |Cite
|
Sign up to set email alerts
|

PMA-induced up-regulation of MMP-9 is regulated by a PKCα-NF-κB cascade in human lung epithelial cells

Abstract: Expression of matrix metalloproteinase-9 (MMP-9) is associated with airway remodeling and tissue injury in asthma. However, little is known about how MMP-9 is up-regulated in airway epithelial cells. In this study, we show that phorbol myristate acetate (PMA) induces MMP-9 expression via a protein kinase Cα (PKCα)-dependent signaling cascade in BEAS-2B human lung epithelial cells. Pretreatment with either GF109203X, a general PKC inhibitor, or Gö6976, a PKCα/β isozyme inhibitor, inhibited PMA-induced activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
69
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 45 publications
5
69
0
Order By: Relevance
“…Activation of PKC by TPA is critical for tumor invasion and MMP-9 induction (7,29). Our previous study showed that activation of PKCa by TPA induced the proliferation and secretion of MMP-2 in fibroblasts and colorectal carcinoma cells (25,30).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of PKC by TPA is critical for tumor invasion and MMP-9 induction (7,29). Our previous study showed that activation of PKCa by TPA induced the proliferation and secretion of MMP-2 in fibroblasts and colorectal carcinoma cells (25,30).…”
Section: Discussionmentioning
confidence: 99%
“…The resultant supernatants were assayed for protein and β-galactosidase activity. Luciferase activity was assayed in 10-μl samples of extract; the luciferase luminescence was counted in luminometer (Turner Design, TD-20/20) and normalized to the co-transfected β-galactosidase activity, as described elsewhere (Woo et al, 2000b;Chung et al, 2005;Shin et al, 2007). Transfection experiments were performed in triplicate with two independently isolated sets of cells, and the results were averaged.…”
Section: Transient Transfection and Nf-κb Luciferase Activity Assaymentioning
confidence: 99%
“…Activation of pro-inflammatory pathways in lung epithelial cells, including the PKC, AP-1, and NF-kB pathways, by bacterial infection are suggested to contribute significantly to pneumonia [4,10,26]. Although L. pneumophila efficiently infects and stimulates lung epithelial cells [4][5][6][7] and GM-CSF has been shown as important for bacteria elimination via phagocytosis, mechanisms of L. pneumophila-induced release of this cytokine are widely unknown.…”
mentioning
confidence: 99%
“…The expression of GM-CSF is controlled by a tight regulatory network involving the transcription-factors nuclear factor (NF)-kB and the activator protein (AP)-1 [24,25]. These transcription factors are activated by complex signalling pathways, including protein kinase C (PKC) [26,27]. PKCs, a family of serine/threonine kinases, are involved in different biological processes.…”
mentioning
confidence: 99%